2023
DOI: 10.3390/molecules28041782
|View full text |Cite
|
Sign up to set email alerts
|

Complete, Theoretical Rovibronic Spectral Characterization of the Carbon Monoxide, Water, and Formaldehyde Cations

Abstract: New high-level ab initio quartic force field (QFF) methods are explored which provide spectroscopic data for the electronically excited states of the carbon monoxide, water, and formaldehyde cations, sentinel species for expanded, recent cometary spectral analysis. QFFs based on equation-of-motion ionization potential (EOM-IP) with a complete basis set extrapolation and core correlation corrections provide assignment for the fundamental vibrational frequencies of the à 2B1 and B̃ 2A1 states of the formaldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 84 publications
2
11
0
Order By: Relevance
“…The resulting QFF utilizing coupled cluster harmonic terms and DFT anharmonic terms is then fed into a second-order vibrational perturbation theory (VPT2) code called pbQFF written in the modern Rust programming language built upon the previous Fortran77 Spectro code. , This produces the anharmonic fundamental vibrational frequencies and the rotational constants utilized for comparison to the experimental benchmarks: NH 2 – , HNO, HOO, HNF, HSO, HSS, H 2 CO, HOCO + , and formic acid. The HNO, HOO, HNF, HSO, and HSS F12-TcCR + EOM excited-state harmonic force constants are from ref . The performance of each method’s frequencies and rotational constants are evaluated as MA%Ds compared to experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting QFF utilizing coupled cluster harmonic terms and DFT anharmonic terms is then fed into a second-order vibrational perturbation theory (VPT2) code called pbQFF written in the modern Rust programming language built upon the previous Fortran77 Spectro code. , This produces the anharmonic fundamental vibrational frequencies and the rotational constants utilized for comparison to the experimental benchmarks: NH 2 – , HNO, HOO, HNF, HSO, HSS, H 2 CO, HOCO + , and formic acid. The HNO, HOO, HNF, HSO, and HSS F12-TcCR + EOM excited-state harmonic force constants are from ref . The performance of each method’s frequencies and rotational constants are evaluated as MA%Ds compared to experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Several composite methods have been proposed in our group of late to address this issue. These most often utilize EOM-CCSD for the excited-state computation but are conjoined to some CCSD­(T) definition of the ground electronic state. While full EOM-CCSDT methods with considerations for complete basis set (CBS) extrapolations (“C”) and core electron correlation (“cC”) provide accurate descriptions in the so-called EOM-CCSDT-CcC approach, they are prohibitively time-consuming for all but the smallest molecules. The use of explicitly correlated approaches in CCSD­(T)-F12b in the ground electronic state combined with EOM-CCSD for the excited state with the addition of scalar relativity (“ R ”) to the CcC considerations shows promise in the F12-TcCR + EOM methodology, which reports mean absolute percent differences (MA%Ds) compared to gas phase experiment of less than 2.5% .…”
Section: Introductionmentioning
confidence: 99%
“…The most cost-effective QFFs are most often computed in a composite approach taking into consideration various factors including core electron correlation, relativity, complete basis set (CBS) extrapolations, full configuration interaction approximations, and even considerations for non-Born–Oppenheimer effects and quantum electrodynamics . However, some of these are exceptionally difficult and time-consuming to compute, leaving the core electrons, relativity, and complete basis set extrapolations as the most commonly employed corrections ,, even for electronically excited states. ,, Similar considerations will be made here for the EOMEE-CCSD­(T)­(a)*.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Some have been based on EOM-CCSD with corrections for triples in EOM-CC3 corrections. , More recently, highly accurate, CCSD­(T) ground state energies corrected with EOM-CCSD excitation energies treated in various ways have produced mixed success for computing QFFs . Inclusion of explicit correlation from the F12 formalism , in the ground state term provides the same level of confidence in the fundamental vibrational frequency predictions but for less computational time. , The use of the ionization potential version of EOM in EOMIP-CCSDT is rigorously the best choice among those tested thus far for computing QFFs, but the scaling of the method and size of the basis sets make these computations impossibly time-consuming save for the smallest molecules or the most efficient supercomputers . Hence, new wave function-based, excited state methods need to be identified in order for application to QFFs if means beyond vibronic variational computations are to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Any hybrid method, though, is really only as good as its underlying harmonic frequencies for QFF VPT2 computations. Recent work has shown that QFFs defined from explicitly correlated coupled cluster theory at the singles and doubles level with perturbative triples (CCSD(T)‐F12) employing a triple‐ζ basis set including core electron correlation and corrected for canonical CCSD(T) scalar relativity (the so‐called F12‐TZ‐cCR or, equivalently, F12‐TcCR method) can provide exceptional accuracy in the computation of anharmonic fundamental vibrational frequencies and rotational constants [48,49]. The increased effective basis set size for a given ζ level in explicit correlation [50] largely removes the need for costly big basis sets needed for CBS extrapolations [51–53].…”
Section: Introductionmentioning
confidence: 99%